On Research Directions in Coexistence Areas of Radar And Communication Systems - Mateusz WRÓBEL; Jan M. KELNER (Communications of International Proceedings, 2021)
This paper focuses on an overview of research directions in the coexistence areas of radars and communication systems. This topic is related to modern passive and multiple-input-multiple-output (MIMO) radar systems that operate in the presence of ubiquitous wireless radio networks, in particular mobile cellular or Wi-Fi networks. We discuss spectrum-sharing issues between communication and radar systems if they use the same or adjacent frequency bands. Until recently, interference between such systems was not a problem, generally. However, with the development of electronics and telecommunications, higher and higher frequency ranges are adopted in both radiolocation and radiocommunication. Hence, one of the trends is the design of dual-function radar-communication systems. This research direction is intended to enable the intelligent use of the same radio resources in different systems. For this purpose, the creation of dedicated waveforms and the appropriate beamforming of antenna systems are used.
Keywords: Radar; Communications; Dual-Function Radar Communication System; Joint Radar-Communications System; Integrated Radar-Communications System; Passive Radar; Coexistence Of Radar And Communication Systems; Spectrum Sharing.